Assessment of LAA strain and thrombus mobility and its impact on thrombus resolution - value of a novel echocardiographic thrombus tracking method. (4th February 2022) - Morais, P; Nelles, D; Vij, V; Al-Kassou, B; Weber, M; Nickenig, G; Schrickel, JW; Vilaca, J; Sedaghat, A
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): FCT – Fundação para a Ciência e Tecnologia Portugal 2020 Partnership Agreement, through the European Regional Development Fund (FEDER) Background: The left atrial appendage (LAA) is the major nidus for thrombus in patients with non-valvular atrial fibrillation. LAA thrombus mobility and changes hereof under anticoagulation may serve as a marker of both risk of embolism and efficacy of treatment. In this study, we hypothesized that LAA dynamics and thrombus mobility could serve as a baseline marker of thrombus dissolvability. Methods: Transesophageal echocardiographic (TEE) images of in whom LAA thrombi were previously diagnosed were evaluated. Each image was tracked using a state-of-the-art tracking toolbox and functional information from the LAA and thrombi extracted. Global LAA motion was quantified through the longitudinal strain, while thrombus mobility was measured through a novel tracking scheme by directly capturing and measuring the thrombus motion isolated from the global cardiac motion. Baseline characteristics and echocardiographic parameters were compared between responders (thrombus resolution, i.e. no thrombus found at follow-up TEE) and non-responders (thrombus persistence or growth, i.e. thrombus found at follow up TEE) groups. Results: 35 patients (54.3% male and 45.7% female) with a mean age of 72.9 ± 14.1 years were included. Atrial fibrillation was present in all patients, showing a high risk for thromboembolism (CHA2DS2-VASc-Score 4.1 ± 1.5). Moderately reduced LVEF (41.7 ± 14.4%) and signs of diastolic dysfunction (E/E' = 19.7 ± 8.5) was found in the cohort. While anticoagulation was initiated in all patients, resolution was achieved in 51.4% of patients. Significantly higher thrombus mobility (0.33 ± 0.13mm vs. 0.18 ± 0.08mm, p < 0.01 – Figure 1A) and LAA peak strain (-3.0 ± 1.3 vs -1.6 ± 1.5%, p < 0.01 – Figure 1B) were observed in responders against the non-responders group. Conclusions: The quantification of the thrombus mobility through a tracking scheme is feasible. In our study population, higher thrombus mobility appeared to be associated with thrombus resolution. Further studies are required to evaluate the additional prognostic of the proposed technique. Figure 1 – Quantification of the thrombus mobility (A) and peak LAA longitudinal strain (B) in both responder (blue) and non-responder group (green). *p < 0.05, unpaired t-test between non-responder and responder groups.